Pengaruh Penggunaan Endorsement dan Inovasi Produk terhadap Keputusan Pembelian pada Online Shop Jamise Syari dalam Perspektif Ekonomi Islam - Wahyuni, Yuyun; Fitriani, Agnes (Valid: Jurnal Ilmiah, 2025)
The purpose of this study was to determine the significance of the influence of the use of endorsements and product innovation on purchasing decisions at the Jamise Syari online shop from an Islamic economic perspective. The population in this study were all consumers of Jamise Syari products. The sampling method in this study used a purposive sampling technique with the criteria that respondents must be followers of the Jamise Syari Instagram account and have purchased the product at least once. The sample taken was 160 respondents. The research instrument test tool used validity and reliability tests. Data analysis used multiple linear regression. Hypothesis testing used the t-test and F-test. The results showed that the use of endorsements and product innovation significantly influenced purchasing decisions at the Jamise Syari online shop from an Islamic economic perspective. This shows that respondents pay close attention to the use of endorsements and product innovation carried out by the Jamise Syari online shop and are considered in making purchasing decisions